The relative age effect in young French basketball players: a study on the whole population - Delorme, N.; Raspaud, M. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The aim of this study is to test the presence of the relative age effect (RAE) and to examine height in an overall population of the young French basketball players from 7 to 18 years old, male (n=151 259) and female (n=107 101). For the boys as for the girls, the results show a statistically significant RAE in all age categories. The effect seems more pronounced during puberty. As far as the height is concerned, players born during quarters 1 and 2 are always significantly taller than those born during quarter 4, apart from the 17-year-old female players. These results require a new look at the methodology in the statistical calculation and the interpretation of RAE. A study wanting to give a precise measurement of this effect will have to take as the expected theoretical distribution the whole population of licensed players in the corresponding years, rather than one on the global population of the country. This will avoid the hasty conclusion that an asymmetric distribution of dates of birth of professional players would be due to RAE, whereas in reality it would be representative of one existing in the population of licensed players.